"Transforming a power plant into an Educational Centre: Agia Small Hydroelectric Power Plant". Issue 1 (1st December 2022) - Bourbourakis, Panagiotis J.; Tsikalakis, Georgios J.
Abstract: Renewable Energy Sources (RES) is the spearhead of the current global energy and technological market. However, RES has been part of our everyday life for many decades. Hydroelectric energy, the prime of the RES's, had a pioneer presence at the non-interconnected island of Crete, where the Small Hydroelectric Power Plant (SHPP) of Agia ceased its operation after eighty years of service. Subsequently, the owner of the plant decided to grant the permission of use of the plant facilities to the Prefecture of Crete and to finance the renovation of the facilities, towards the design and erection of a museum and information center for the Renewable Energy Sources, for the Culture of Water and for the promotion of "acting green". Furthermore, the information center, combined with the amazing natural environment and adjacent ecosystem of Lake Agia, create a sightseeing of high educational and ecological interest. In the project, we highlight a good example of utilizing the infrastructure and facilities of a past Renewable Energy Sources Power Plant and transforming it into an Educational Centre, focusing on environmental sustainability and education.